2015
DOI: 10.1149/06801.2119ecst
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing for Solid Oxide Cell Electrode Fabrication

Abstract: Additive manufacturing can potentially offer a highly-defined electrode microstructure, as well as fast and reproducible electrode fabrication. Selective laser sintering is an additive manufacturing technique in which three-dimensional structures are created by bonding subsequent layers of powder using a laser. Although selective laser sintering can be applied to a wide range of materials, including metals and ceramics, the scientific and technical aspects of the manufacturing parameters and their impact on mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…So far, AM has been demonstrated for the fabrication of flow field plates and gas diffusion layers (GDL) in PEMFCs, which act as an ionic conductor and reactants facilitator, respectively. Although some studies have reported 3D printed membranes and catalyst layers , , , they were, however, not directly demonstrated in a PEMFC system. Besides, graphene aerogel (GA) has drawn lots of research interests used as flow field plates and gas diffusion layers in the direct methanol fuel cells .…”
Section: Fuel Cell Advances Enabled By Am Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, AM has been demonstrated for the fabrication of flow field plates and gas diffusion layers (GDL) in PEMFCs, which act as an ionic conductor and reactants facilitator, respectively. Although some studies have reported 3D printed membranes and catalyst layers , , , they were, however, not directly demonstrated in a PEMFC system. Besides, graphene aerogel (GA) has drawn lots of research interests used as flow field plates and gas diffusion layers in the direct methanol fuel cells .…”
Section: Fuel Cell Advances Enabled By Am Technologiesmentioning
confidence: 99%
“…Lomberg et al. reported the fabrication of the anode with hierarchical porous microstructures enabled by SLS . The results showed that SLS has the potential to create bespoke electrode with well‐designed microstructure by manipulating the laser speed and laser power .…”
Section: Fuel Cell Advances Enabled By Am Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the stability of materials and designing more poison resistant materials will further extend the life of the fuel cell. The exiting developments in manufacturing – additive manufacturing/3D printing – offer new opportunities for fuel cells design and manufacture, and for materials R&D in the field . Reversible fuel cells, operating both as electrolysers and fuel cells, or SOFC‐based high temperature electrolysers are gaining significant interest for storing renewable electricity …”
Section: Summary and Futurementioning
confidence: 99%
“…To bring this potential fuel cell technology closer to commercialization, there is a need to fabricate these devices with suitable up-scalable technologies such as printing methods. Digital manufacturing has been recently introduced to fabricate ceramic fuel cells [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Digital manufacturing offers various advantages over conventional printing techniques such as screen printing [ 38 , 39 ] and tape casting [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%